Моделювання електромагнітно – акустичного перетворювача - Сучков, Григорій Михайлович; Десятніченко, Олексій Володимирович (НТУ "ХПІ", 2008)
Проведен анализ математических моделей електромагнитно – акустического преобразователя. Предложены методы построения моделей. Приведены результаты исследований построенных моделей, сравнение с данными реальных измерений. Выделены недостатки, предложены пути повышения качества моделирования.

The analysis of some variants of mathematical model electomagnetic – acoustic converter is carried out. Methods of construction of such model are offered. Results of researches of the constructed models, comparison with the data of real measurements are resulted. Lacks are allocated, ways of increase of reliability of modelling are offered.
Keywords: методи контролю; ЕМАП; об’єкт контролю; ОК; сигнал; робоча зона